2023
DOI: 10.3390/coatings13040772
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Zn-Fe Alloy Coatings and Their Corrosion Resistance

Abstract: Single-layer and multilayer alloy deposits were coated onto a mild steel substrate by a single-bath electroplating process. The developed coating consists of Zn and Fe alloys having different compositions with different layers. The anticorrosion behavior of single-layer and multilayer deposits was evaluated by the potentiodynamic polarization method. The surface morphology of the deposits was studied with a scanning electron microscope. The crystal structure of the deposits was analyzed with the X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…This study finding (in which almost crack-free coatings showed better pitting corrosion resistance) is in agreement with previous results of Chien C.W. et al [ 17 ] and Ghaziof S. et al [ 45 ] and others [ [46] , [47] , [48] ], who reported that coating defect like crack is detrimental to the integrity of coatings and should be eliminated as much as possible for an effective application.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…This study finding (in which almost crack-free coatings showed better pitting corrosion resistance) is in agreement with previous results of Chien C.W. et al [ 17 ] and Ghaziof S. et al [ 45 ] and others [ [46] , [47] , [48] ], who reported that coating defect like crack is detrimental to the integrity of coatings and should be eliminated as much as possible for an effective application.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…It may be attributed to the increase of Fe content and the cracks in the coating at higher current densities. 47,48 All the corrosion currents of the HEA coatings were lower than that of 304 stainless steels (135.2 μA cm −2 ). On the other hand, the values of polarization resistance (R p ) were obtained by fitting the Tafel curves.…”
Section: Resultsmentioning
confidence: 94%
“…38 Electrodeposition can be used to generate not only interfacial alloys such as Ni on Au(111) but also alloyed coatings to impart specific properties and change the appearance of an object. One modern aspect of electrodeposition involves the square pulse current sequence procedure 39 to fabricate a number of compositionally modulated multilayered materials, such as ZnFe, 40 ZnCo, 41 and ZnNi, 18,42 on mild steel and others. These alloyed nanocoatings have unique microstructures and electronic properties, eventually leading to superior corrosion resistance.…”
Section: Ni Deposition On Au(111) Without MMImentioning
confidence: 99%